Toxicological aspects of cannabinoid, pesticide and metal levels detected in light Cannabis inflorescences grown in Italy. (October 2021) - Amendola, G.; Bocca, B.; Picardo, V.; Pelosi, P.; Battistini, B.; Ruggieri, F.; Attard Barbini, D.; De Vita, D.; Madia, V.N.; Messore, A.; Di Santo, R.; Costi, R.
Abstract: Recently, the cultivation of light Cannabis, with a total THC content less than 0.6%, has been encouraged due to its industrial and therapeutic potential. This has increased the consumption of hemp for both smoking purposes and food preparation. Even so, Cannabis inflorescences are not subject to EU regulations and standards provided for food and tobacco products. A study was carried out on thirty-one inflorescences samples, collected in different Italian regions, in order to determine cannabinoids, pesticides and metals and to evaluate the exposure of consumers to contaminants and ensure a safe consumption. Contents of THC were always below 0.5%, while CBD ranged between 0.3 and 8.64%. The determination of 154 pesticides showed that 87% of the samples contained fungicides and insecticides in the range 0.01–185 μg/g. The most found are spinosad and cyprodinil. The concentration of metals ranged from 1 to more than 100 μg/g and As, Cd, Co, Cr, Hg, Cu, Mo, Ni and V exceeded the regulatory US limits for inhaled Cannabis products, while Pb exceeded them for both oral and inhaled products. These contaminants are intrinsically toxic and may affect public health. Actions are needed to establish regulatory measures and reduce the adverse effects caused by contaminants in Cannabis . Graphical abstract: Image 1 Highlights: Tetrahydrocannabinol (THC), cannabidiol (CBD), pesticides and metals were detected in light Cannabis inflorescences. Pesticides, like fungicides and insecticides, were found in 87% of samples. Metals showed levels exceeding the permissible limits in several samples. The high concentrations of pesticides and metals represent a health risk for consumers.